2017
DOI: 10.1186/s12936-017-1772-5
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-rich domains of Plasmodium falciparum SURFIN4.2 and Plasmodium vivax PvSTP2 interact with membrane skeleton of red blood cell

Abstract: Background Plasmodium falciparum dramatically alters the morphology and properties of the infected red blood cells (iRBCs). A large group of exported proteins participate in these parasite-host interactions occurring at the iRBC membrane skeleton. SURFIN4.2 is one of iRBC surface protein that belongs to surface-associated interspersed protein (SURFIN) family. Although the intracellular tryptophan-rich domain (WRD) was proposed to be important for the translocation of SURFINs from Maurer’s clefts to iRBC surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…SURFIN4.2 is a merozoite rhoptry neck protein found at the surface of infected red blood cells (RBCs) (Mphande et al., 2008; Winter et al., 2005) and IP experiments showed that it forms a complex together with the parasite surface protein Glutamate Rich Protein (GLURP) and RON4 giving the name SURGE (SURFIN4.2‐ R ON4‐ G LURP compl E x) to this complex (Quintana et al., 2018). The Tryptophan‐rich domain (WRD) of SURFIN4.2 might bind to cytoskeletal RBC proteins such as actin and spectrin (Zhu et al., 2017) linking the parasite PM to the RBC cytoskeleton. The rhoptry‐associated Adhesin (PfRA) conserved across multiple Plasmodium species is a rhoptry bulb protein involved in the invasion (Anand et al., 2016).…”
Section: Mechanisms Of Invasionmentioning
confidence: 99%
“…SURFIN4.2 is a merozoite rhoptry neck protein found at the surface of infected red blood cells (RBCs) (Mphande et al., 2008; Winter et al., 2005) and IP experiments showed that it forms a complex together with the parasite surface protein Glutamate Rich Protein (GLURP) and RON4 giving the name SURGE (SURFIN4.2‐ R ON4‐ G LURP compl E x) to this complex (Quintana et al., 2018). The Tryptophan‐rich domain (WRD) of SURFIN4.2 might bind to cytoskeletal RBC proteins such as actin and spectrin (Zhu et al., 2017) linking the parasite PM to the RBC cytoskeleton. The rhoptry‐associated Adhesin (PfRA) conserved across multiple Plasmodium species is a rhoptry bulb protein involved in the invasion (Anand et al., 2016).…”
Section: Mechanisms Of Invasionmentioning
confidence: 99%
“…SURFIN4.2 is the best characterized member. It can interact with F-actin and spectrin through its internal domain and be co-transported with PfEMP1 and RIFIN to the surface of infected erythrocytes [ 17 , 18 ]. Analysis of the expression of SURF members revealed that SURFIN4.2 was highly transcribed at the ring stage, while SURFIN8.1, 8.2, 8.3, 1.3, and 14.1 were maximally expressed at the trophozoite stage (Additional file 8 : Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…From these studies, the indication is that these SURFINs may be important to malaria parasites because the antibody to SURFIN 4.2 was found to inhibit merozoite invasion and rosetting formation [ 6 , 11 ]. Therefore, the function of SURFIN 1.1 may involve merozoite invasion as the SURFIN 4.2 [ 27 ]. However, the function and molecular basis of SURFIN 1.1 need to be further clarified.…”
Section: Discussionmentioning
confidence: 99%